Disruption of DYRK1A-induced hyperphosphorylation of amyloid-beta and tau protein in Alzheimer’s disease: An integrative molecular modeling approach - Shukla, Rohit; Kumar, Anuj; Kelvin, David J.; Singh, Tiratha Raj (Frontiers in Molecular Biosciences, 2023)
Alzheimer's disease (AD) is a neurological disorder caused by the abnormal accumulation of hyperphosphorylated proteins. Dual specificity tyrosine-phosphorylation-regulated kinase 1A (DYRK1A) is a dual phosphorylation enzyme which phosphorylates the amyloid-β (Aβ) and neurofibrillary tangles (NFTs). A high throughput virtual screening approach was applied to screen a library of 98,071 compounds against DYRK1A using different programs including AutoDock Vina, Smina, and idock. Based on the binding affinities, we selected 330 compounds for absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis. Various pharmacokinetics parameters were predicted using the admetSAR server and based on the pharmacokinetics results, 14 compounds were selected for cross docking analysis using AutoDock. Cross docking analysis revealed four compounds, namely ZINC3843365 (-11.07 kcal/mol−1), ZINC2123081 (-10.93 kcal/mol−1), ZINC5220992 (-10.63 kcal/mol−1), and ZINC68569602 (-10.35 kcal/mol−1), which had the highest negative affinity scores compared to the ten other molecules analysed. Density functional theory (DFT) analysis was conducted for all the four top-ranked compounds. Molecular interactions stability of these four compounds with DYRK1A have been evaluated using molecular dynamics (MD) simulations on 100 nanoseconds followed by principal component analysis (PCA) and binding free energy calculations. The Gibbs free energy landscape analysis suggested the metastable state and folding pattern of selected docking complexes. Based on the present study outcome, we propose four antagonists viz ZINC3843365, ZINC2123081, ZINC5220992, and ZINC68569602 as potential inhibitors against DYRK1A and to reduce the Aβ and NFTs burden. These screened molecules can be further investigated using a number of in-vitro and in-vivo experiments.